Solution-focused approach to Social Work practice - Riera Adrover, Joan Albert; Campos Vidal, José Francisco; Cuartero Castañer, María Elena (Cuadernos de Trabajo Social, 2022)
Intervention models based on constructivism have proliferated in social work practice. A focus on people’s resources and collaboration has reflected the link between solution-focused approaches and the values of social work. This article contains an in-depth analysis of the studies that have examined the solution-focused approach as a model of intervention in social work practice. The main results concern the possibility of raising people’s voices. This involves references to constructivism and social constructionism; approaches to linguistic practices and the creation of meanings; increased culturally-based resources; the position of not knowing, supported by the recognition of people as experts in the situation; curiosity and the approach to contextual knowledge; resistance as a form of cooperation; times when the problem has no influence; as well as adjustments to what people expect from professionals. Relevant recommendations are provided.